Comparison of morphological, immunohistochemical, and molecular genetic features of inflammatory fibroid polyps (Vanek's tumors) - Daum, Ondrej; Hatlova, Jana; Mandys, Vaclav; Grossmann, Petr; Mukensnabl, Petr; Benes, Zdenek; Michal, Michal (Virchows Archiv, 2010)
Vanek's tumor (inflammatory fibroid polyp) is a rare benign lesion occurring throughout the digestive tract. Histologically, two patterns can be recognized. Classical Vanek's tumor contains concentric formations of proliferating spindle cells which are CD34 positive. Atypical, inflammatory pseudotumor-like Vanek's tumor lacks concentric formations and is CD34 negative. Recently, mutations in platelet-derived growth factor receptor alpha (PDGFRA) were reported in gastric and small intestinal Vanek's tumors. In this study, KIT exons 9, 11, 13, and 17, PDGFRA exons 12, 14, and 18, and a part of exon 15 BRAF for point mutation V600E were screened in 23 cases of Vanek's tumor, both classical (n = 16) and inflammatory pseudotumor-like (n = 7). No mutations in all analyzed exons of KIT and BRAF and in exon 14 of PDGFRA were detected. Six Vanek's tumors harbored activating mutations in PDGFRA exons 12 (n = 5) and 18 (n = 1) respectively: S566_E571delinsK (n = 1), S566_E571delinsR (n = 4), and D842 del (n = 1). The mutations were detected in the classical (n = 5), as well as inflammatory pseudotumor-like (n = 1) Vanek's tumors. The results of this study suggest that the two morphological patterns of Vanek's tumor more probably represent only variants of one type of tumor than two different lesions. Furthermore, BRAF mutations were not shown to drive growth of PDGFRA wild-type Vanek's tumors.
Keywords: senioři; gastrointestinální trakt; nemoci střev; leiomyom; Polyps; senioři nad 80 let; Leiomyoma; Middle Aged; Gastrointestinal Tract; mužské pohlaví; Exons; Receptor, Platelet-Derived Growth Factor alpha; mutace; Stomach Diseases; Adult; Aged, 80 and over; růstový faktor odvozený z trombocytů - receptor alfa; ženské pohlaví; Mutation; Humans; Proto-Oncogene Proteins B-raf; polypy; lidé středního věku; Intestinal Diseases; protoonkogenní proteiny B-Raf; nemoci žaludku; dospělí; Female; Aged; exony; lidé; Male